2012
DOI: 10.3174/ajnr.a2915
|View full text |Cite
|
Sign up to set email alerts
|

Results of Screening for Intracranial Aneurysms in Patients with Coarctation of the Aorta

Abstract: BACKGROUND AND PURPOSE: IAs are found in 2.3% of adults; the mean age at detection is 52 years. Prevalence is Ͻ0.5% in young adults. Early studies suggest that 10%-50% of patients with aortic coarctation have IAs. Screening recommendations are variable. We sought to examine the prevalence of IAs through screening with MRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 36 publications
2
51
3
Order By: Relevance
“…30 There is a theoretic potential risk of IA rupture with increasing cerebral perfusion pressure by occluding the aorta, albeit temporarily. 3 Surgeons should be aware of the presence of an IA to avoid large pressure variations. In addition, measures such as strict postoperative blood pressure control can also be taken with a known IA, to reduce the risk of rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 There is a theoretic potential risk of IA rupture with increasing cerebral perfusion pressure by occluding the aorta, albeit temporarily. 3 Surgeons should be aware of the presence of an IA to avoid large pressure variations. In addition, measures such as strict postoperative blood pressure control can also be taken with a known IA, to reduce the risk of rupture.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous studies have identified a link between intracranial aneurysms and aortic diseases such as coarctation of the aorta or a bicuspid aortic valve. [3][4][5][6] A few studies have reported an association between abdominal aortic aneurysms and thoracic aortic aneurysms and IAs, with a higher prevalence of IA in patients with aortic aneurysms. [6][7][8][9][10][11][12][13][14] However, contrary to other pathologies such as autosomal dominant polycystic kidney disease (ADPKD), which is associated with IA in 12.4% of cases, no systematic screening for IA is proposed for patients with AA.…”
mentioning
confidence: 99%
“…The upper extremity systolic BP is usually 20 mm Hg higher than the lower extremities in patients with significant CoA. In rare instances of CoA patients with concomitant anomalous subclavian artery origin distal to the site of CoA, systolic BP differences may not be detected between ipsilateral arm and legs [16].…”
Section: Clinical Presentation -Diagnosismentioning
confidence: 99%
“…378 Diagnosis is more common at an older age in the CoA population (median age of individuals with aneurysm versus without aneurysm, 37 versus 23 years). 379 Individuals with CoA and hypertension appear to have a 2-fold higher incidence of intracranial aneurysm, suggesting increased hypertension with age or perhaps a pathophysiological factor influencing aneurysm formation, although much more data are needed to assess correlation. 379 More recent studies suggest that in children treated early for CoA, there is no clear association of CoA and intracranial aneurysm, but they perhaps still support the possibility that hypertension may contribute to aneurysm development in adults with CoA.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%